2003
DOI: 10.1016/s1044-0305(03)00122-3
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an in vitro insulin receptor substrate-1 phosphorylation site by negative-ion μLC/ES-API-CID-MS hybrid scan technique

Abstract: Recently, we reported a fast on-line alkaline micro-liquid chromatography/electrosprayatmospheric pressure ionization/collision-induced dissociation/mass spectrometric approach for sensitive phosphopeptide screening of a tryptic digested protein and subsequent characterization of the identified phosphopeptide. Based on this study, we now applied an improved method for the identification of phosphorylation sites in insulin receptor substrate 1, an important mediator in insulin signal transduction which was phos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
24
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 23 publications
(10 reference statements)
1
24
1
Order By: Relevance
“…357 of IRS-1 in vitro by Greene et al (41) and our group using the previously described mass spectrometry-based identification procedure (43). The sequence homology of rodent and human IRS-1 is shown in Fig.…”
Section: Identification Of Ser 357 As a Novel Phosphorylation Site Inmentioning
confidence: 96%
“…357 of IRS-1 in vitro by Greene et al (41) and our group using the previously described mass spectrometry-based identification procedure (43). The sequence homology of rodent and human IRS-1 is shown in Fig.…”
Section: Identification Of Ser 357 As a Novel Phosphorylation Site Inmentioning
confidence: 96%
“…Site of PKC-in IRS-1-By developing a novel mass spectrometric approach for phosphopeptide screening out of complex phosphoprotein digest mixtures, we recently identified Ser 318 as a PKC-in vitro phosphorylation site in the IRS-1 N2 fragment (IRS-1 sequence from amino acid 265-522) (14). To search for further in vitro PKC-phosphorylation sites in IRS-1 not covered by the N2-fragment, the PKC--catalyzed 32 P-incorporation in the NH 2 terminal 1 (IRS-1-N1), NH 2 terminal 2 (IRS-1-N2), the middle (IRS-1-M), and the C-terminal part (IRS-1-C) were compared ( Fig.…”
Section: Identification Of the Major In Vitro Phosphorylationmentioning
confidence: 99%
“…1C). According to our previously published procedure (14), mass spectrometric peptide sequencing revealed that more than 85% of total incorporated 32 P-radioactivity is based upon peaks of different variants of the monophosphorylated phospho-Ser 318 . Consequently, these peaks were not 32 P-phosphorylated in the HPLC-separated, mutated GST-Ala 318 -IRS-1 N2 digest.…”
Section: Identification Of the Major In Vitro Phosphorylationmentioning
confidence: 99%
See 2 more Smart Citations